2024
DOI: 10.26599/fshw.2022.9250086
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency and safety evaluation of hemoglobin hydrolysate as a non-heme iron fortifier

Abstract: Hemoglobin hydrolysate is derived from the enzymatic degradation of hemoglobin. This work aimed to evaluate whether hemoglobin hydrolysate promotes the absorption of non-heme iron and the safety of absorbed iron in mice by analyzing the iron binding content, iron circulation, and liver homeostasis. We found that hemoglobin hydrolysate promoted the absorption of non-heme iron with high efficiency in duodenum by spontaneously binding non-heme iron during digestion, and increased hepatic iron content by up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…It has been reported that hemoglobin hydrolysate diet and heme diet significantly raised the iron contents in duodenum. [ 43 ] The increase in iron content significantly reduced the L. reuteri content in duodenal contents. [ 44 ] In this study, the impact of completely digested myoglobin on L. reuteri may be attributed to hemin and peptides.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hemoglobin hydrolysate diet and heme diet significantly raised the iron contents in duodenum. [ 43 ] The increase in iron content significantly reduced the L. reuteri content in duodenal contents. [ 44 ] In this study, the impact of completely digested myoglobin on L. reuteri may be attributed to hemin and peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the concentration of unsaturated iron binding capacity (UIBC) derived from our previous research. 15 A A )…”
Section: Preparation Of Peptide−iron Complexmentioning
confidence: 99%
“…When it was observed under the microscope that the adherent area of cells reached 80%, the complete medium was removed, and 1 mL of complete medium containing peptide−iron complex was added, and the cells were incubated at 37 °C for 24 h. Then, the supernatant of the cell culture was collected. The iron content in the supernatant was determined according to the method of Xue et al 15 with some modifications. Briefly, the supernatant was diluted with ultrapure water, and the iron content was quantified using an inductively coupled plasma mass spectrometer (NexION 2000, PerkinElmer, USA).…”
Section: Determination Of Iron Contentmentioning
confidence: 99%
See 2 more Smart Citations